Validation of the Chinese Version of Penn Alcohol Craving Scale for Patients With Alcohol Use Disorder - Ko, Yu-Yu; Fang, Su-Chen; Huang, Wei-Chien; Huang, Ming-Chyi; Chang, Hu-Ming (Psychiatry investigation, 2024)
Objective The Penn Alcohol Craving Scale (PACS) is a five-item, single-dimension questionnaire that is used to measure a patient’s alcohol craving. We sought to develop the Chinese version of the PACS (PACS-C) and assess its reliability and validity.Methods A total of 160 Taiwanese patients with alcohol use disorder were enrolled in this study. The internal consistency and concurrent validity of the PASC-C with the visual analogue scale (VAS) for craving, the Yale–Brown Obsessive Compulsive Scale for heavy drinking (YBOCS-hd), and the Severity of Alcohol Dependence Questionnaire (SADQ) were assessed. The test–retest reliability of the PASC-C was evaluated 1 day after the baseline measurements. Confirmatory factor analysis (CFA) was performed to examine the psychometric properties of the PACS-C.Results The PACS-C exhibited good internal consistency (Cronbach’s α=0.95) and test–retest reliability (r=0.97). This scale showed high correlations with the VAS (r=0.81) and YBOCS-hd (r=0.81 and 0.79 for the obsession and compulsion subscales, respectively), and moderate correlation with the SADQ-C (r=0.47). Furthermore, CFA results revealed that the PACS-C had good fit indices under various models.Conclusion The PACS-C appears to be a reliable and valid tool for assessing alcohol craving in patients with alcohol use disorder in Taiwan.